Particle Flux in the Deep Sargasso Sea: The 35-Year Oceanic Flux Program Time Series - Maureen H. Conte; J.C. Weber (Oceanography, 2014)
The Oceanic Flux Program (OFP) sediment trap time series, the longest running time series of its kind, has continuously measured particle fluxes in the deep Sargasso Sea since 1978. OFP results provided the first direct observation of seasonality in the deep ocean, and they have documented the tight coupling between deep fluxes and upper ocean processes and the intensity of biological reprocessing of sinking flux in the ocean interior. The synergy among OFP and other research programs co-located at the Bermuda time-series site has provided unprecedented opportunities to study the linkages among ocean physics, biology, and chemistry; particle flux generation; and particle recycling in the ocean interior. The OFP time series is beginning to reveal how basin-scale climatic forcing, such as the North Atlantic Oscillation, affects the deep particle flux.